STRUCTURING RESILIENCE IN THE CONTEXT OF COMMON SECURITY AND DEFENCE POLICY - ILINCA, Dragoș (Strategic Impact, 2023)
Resilience is a dimension with a pronounced multidisciplinary character covering a wide range of areas of society, which gives it a fluid profile and difficult to fit into a conceptual-functional typology. The interest in resilience is undoubtedly one of the trends of the current decade, however precursory elements are found throughout history in the most diverse forms of manifestation. As in the case of other dimensions explored in recent years from the perspective of European cooperation in the field of security and defence, resilience was quickly integrated into the steps carried out under the auspices of the Common Security and Defence Policy (CSDP), becoming one of the key objectives of the European Union’s external action toolkit and, last but not least, of the operational commitments carried out globally by this organization. The contribution of the EU Global Security Strategy (EUGS) in designing resilience as a central element of the European security and defence cooperation agenda was defining. The main direction promoted by the EUGS was to strengthen resilience aspects in external action, while taking a structured approach to exploring options for strengthening internal resilience. Subsequently, the outbreak of the war in Ukraine as a result of Russia’s aggression additionally valued the strategic significance of states’ resilience and, subsequently, the importance of the EU’s contribution in this direction. This study is aiming to bring into light the way in which CSDP answers to the challenge of consolidating the resilience. In this vein, the methodological approach that was implemented responded the multidisciplinary character of this topic. In order to consolidate the comprehensive character of the present study, a historical perspective has been used that correlates the evolution of resilience in EU context with the development of various CSDP instruments. In this sense, an important direction of research is represented by the interaction between resilience and EU’s external action and how the EU response to crisis situations has evolved. To a similar extent, this paper approached the resilience from the perspective of internal security of European Union, especially in the context of the war in Ukraine. A special note is made on how the latest EU strategic document (Strategic Compass) placed resilience as being one of the strategic objectives of CSDP. Given all of these aspects, the main conclusions of the article are emphasising the importance of adequate calibration of national approach in generating resilience, not only in the conceptual area but also on the practical aspects such as capabilities and resources required by a strong resilience. At the same time, a special attention is given to how the partnership and external interaction, especially between EU and NATO, are tailored to enhance and complement the national contributions in the field of resilience.